A COMPARATIVE STUDY TO EVALUATE THE EFFECT OF BHRAMARI PRANAYAMA AND NADISHODANA PRANAYAMA ON QUALITY OF SLEEP IN GERIATRIC AGE GROUP. (International Journal of Food and Nutritional Sciences, 2025)
Ageing is the natural process and should be regarded as a normal biological phenomenon associated with physiological, psychological changes. In India, people aged 60 years and above are treated as old. Psychological changes in old age can leads to the changes in the quality of sleep. In Geriatric people undiagnosed and untreated insomnia can cause impaired daily activity and reduced quality of life. According to ayurveda ageing is outcome of kala or parinama and described under ‘Svabhavabalapravrittavyadhi’. In Ayurveda Nidra is included under the Trayopasthamba, A quality sleep will resolve the physical and psychological problems of old age people. Modern medicine offers numerous medications to enhance sleep; however, these often come with side effects. As a result, non-pharmacological interventions are increasingly necessary. One effective approach is Pranayama, particularly techniques like Nadishodhana and Bhramari pranayama. These practices can help to calm the nervous system in older adults, leading to improved sleep quality and a better overall quality of life.